Vapor-liquid equilibria for the binary system difluoromethane (HFC-32) plus propane (HC-290) at seven temperatures [(268.15, 278.15, 283.15, 288.15, 298.15, 308.15, and 318.15) K] - Lee, BG; Yang, WJ; Kim, JD; Lim, JS (AMER CHEMICAL SOC, 2003)
Isothermal vapor-liquid equilibria for the binary mixtures of difluoromethane (HFC-32) + propane (HC-290) were measured at (268.15, 278.15, 283.15, 288.15, 298.15, 308.15, and 318.15) K. The experiments were carried out using a circulation-type equilibrium apparatus with the measurement of temperature, pressure, and the compositions of the liquid and vapor phases. The experimental data were correlated with the Peng-Robinson equation of state using the Wong and Sandler mixing rules and the Carnahan-Starling-Desantis equation of state. Calculated results with these equations showed good agreement with the experimental data, but the Peng-Robinson equation of state gave more accurate calculations for the binary systems. It was found that this system has a very strong positive azeotrope for all the temperature range studied here.
Keywords: ALTERNATIVE REFRIGERANT MIXTURES; PHASE-EQUILIBRIA; MIXING RULE; HFC-134A; STATE; HFC-152A; EQUATION; ISOBUTANE; HFC-227EA; PRESSURE